Tax Amnesty Program and Company Value with EVA Momentum Perspective on Stock Price - Sari, Diana; Mahtiani, Feni (International Journal of Psychosocial Rehabilitation, 2020)
Companies listed on the capital market are supported by two factors, namely internal factors and external factors. In this study, one of the externals is tax amnesty, which is a government program to improve the income state and have an impact on the capital market. Company value is an internal factor that can influence investors perceptions of the company. Tax Amnesty Program and Company Value with EVA Momentum Perspective on Stock Price. The research sample is a manufacturing company registered on the Stock Exchange in 2016-2017 that follows the tax amnesty program. To achieve the research objectives, the method used in this study is a descriptive method of analysis with quantitative discussion. The results of the study showed that using the tax amnesty multiple regression model and the company's value on stock prices.